NON-AXISYMMETRIC PERPENDICULAR DIFFUSION of CHARGED PARTICLES and THEIR TRANSPORT ACROSS TANGENTIAL MAGNETIC DISCONTINUITIES - R. D. Strauss (2018)
© 2016. The American Astronomical Society. All rights reserved.. We investigate the transport of charged particles across magnetic discontinuities, focusing specifically on stream interfaces associated with co-rotating interaction regions in the solar wind. We argue that the magnetic field fluctuations perpendicular to the magnetic discontinuity, and usually also perpendicular to the mean magnetic field, are strongly damped in the vicinity of such a magnetic structure, leading to anisotropic perpendicular diffusion. Assuming that perpendicular diffusion arises from drifts in a turbulent magnetic field, we adopt a simplified approach to derive the relevant perpendicular diffusion coefficient. This approach, which we believe gives the correct principal dependences as expected from more elaborate calculations, allows us to investigate transport in different turbulent geometries, such as longitudinal compressional turbulence that may be present near the heliopause. Although highly dependent on the (possibly anisotropic) perpendicular length scales and turbulence levels, we generally find perpendicular diffusion to be strongly damped at magnetic discontinuities, which may in turn provide an explanation for the large particle gradients associated with these structures.